2016
DOI: 10.3832/ifor1657-008
|View full text |Cite
|
Sign up to set email alerts
|

The forest biodiversity artery: towards forest management for saproxylic conservation

Abstract: One of the objectives of forest conservation is the set aside of unharvested areas. However, the fragmentation and lack of connectivity of protected areas make the integration of conservation measures in productive forests essential. Strategies to integrate conservation of saproxylic biodiversity in forest management have been developed, but often considering only specific aspects or remaining preliminary otherwise. As the impact of climate change and anthropogenic stresses increases, the development and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 125 publications
0
25
0
3
Order By: Relevance
“…As snags are future downed wood, the retention of large trees as future snags is recommended in managed forests to sustain wildlife populations that depend on these resources. A careful management of dead wood in actively managed forests may contribute to the conservation of biodiversity at the local level, and may allow to connect productive stands with forest area aimed to conservation (Mason & Zapponi 2015).…”
Section: Resultsmentioning
confidence: 99%
“…As snags are future downed wood, the retention of large trees as future snags is recommended in managed forests to sustain wildlife populations that depend on these resources. A careful management of dead wood in actively managed forests may contribute to the conservation of biodiversity at the local level, and may allow to connect productive stands with forest area aimed to conservation (Mason & Zapponi 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous wildlife functions depend on decaying wood as a source of food, nutrients and protection for organisms at diverse trophic levels [72,[75][76][77][78]. Suitable density and different decay stages of snags are critical for the preservation of biodiversity and the constant functionality of forest ecosystems [40,79]. Müller et al [68] observed that many saproxylic beetles benefit from former fungal colonization, increasing species numbers in higher stages of wood decay.…”
Section: Decay Class Of Cwdmentioning
confidence: 99%
“…1-Objects of the real world are organized in complex units made of smaller systems embedded in larger ones (theory and examples in natural environments, papers in English, French or Italian: Odum, 1953Odum, , 1997Johnson, 1998;Botkin, 1990;Zanella, 1995Zanella, , 1996Camaret et al, 2000;Saugier et al, 2001;Begon et al, 2005; few among many possible examples in forest ecosystems: Susmel et al, 1976;Susmel, 1980Susmel, , 1988Oldeman, 1990;Zanella, 1994;Carletti et al, 2009;Nocentini, 2011;Mason and Zapponi, 2015). Concerning humus systems, we would like to classify humus profiles observing features detectable in the field by the naked eye or with a 10×-magnifying lens.…”
Section: A Functional Classificationmentioning
confidence: 99%